O regime geral de previdência social: diagnósticos estruturais críticos e proposta de reformas - Cordeiro, Gustavo Faria (2006)
Since the last decade of the past century and further, there have been increased, polemic discussions in Brazil that are also occurring simultaneously in the rest of the world: the sustainability of public pension systems. The Brazilian system, which is denominated as the General Regimen of Social Welfare and was established in a distribution regimen, is becoming a growing source of expenditures for the Federal Government and is contributing to the increasing of its fiscal deficit. This situation started to decline after the promulgation of the Federal Constitution in 1988, in which actions had been established reflecting the feeling of ¿social debt¿ existing in the country by that time after years of economic growth without yield redistribution. Thus, benevolent rules had been instituted that provided an assistancialist character to the program, making it unsustainable when it is seen by the internationally accepted premise of the pension system as social insurance with perpetual duration. In consequence, there was an explosive growth of the financial needs of the system reaching the equivalent of 1.63% of the Gross Domestic Product in 2005. In this sense, many arguments in favor of revision and reforms in the current model had solidified, resulting, in 1998, in some changes in the contribution rules of the diverse sectors of society, as well as in the concession of benefit rules. However, such changes had not obtained significant effects since the main source of the imbalance, which is essentially structural, was not attacked. Therefore, this research seeks to diagnose some of the most structural points in the current public pension system in Brazil and evaluate what can be done in terms of reforms to turn the program into balance again and in restore harmony with its conceptual objectives.